Growth of dwarf castor hybrids at different soil bulk densities - Zoz, Tiago; de Castro Seron, Cássio; da Silva Oliveira, Carlos Eduardo [UNESP]; Dutra Zanotto, Maurício [UNESP]; Maior Bono, José Antônio; Barreto Aguiar, Eduardo; Wilson Witt, Travis (Elsevier, 2021)
Soil compaction becomes a frequent problem due to the increased traffic of large agricultural machines and implements necessary for crop management. Soil compaction, characterized by increased soil bulk density, prevents root growth, and consequently, the absorption of water and nutrients. Castor may be an alternative crop for cultivation in soils with a compaction problem because it has a vigorous root system that could break the compacted soil layers, consequently improving the soil quality for the next growing season. This study aimed to evaluate the growth of dwarf castor hybrids under different soil bulk density levels. A randomized block design with four replications in a 4 × 5 factorial scheme was used. Four castor genotypes were evaluated (two hybrids and two cultivars) under five soil bulk densities: 1.09; 1.30; 1.51; 1.72 and 1.93 Mg m−3. The plants were grown in pots assembled from three overlapping 200 mm diameter polyvinyl chloride (PVC) rings until 56 days after emergence. There was no interaction among the soil bulk density and castor genotypes for all variables. The genotypes had the same behavior under high soil bulk density conditions, and similar values were observed of shoot and root dry matter partitioning in the three soil layers between dwarf castor hybrids and castor cultivars. The genotypes accumulated from 68–71% of dry mass in the shoot, and the remaining (29–32 %) was accumulated in the roots. The highest root and shoot dry matter accumulations were estimated with soil bulk density around 1.60 Mg m−3. The results suggest that castor can be grown in areas with soil compaction problems.
Keywords: Genotypes; Ricinus communis L.; Root system; Soil compaction